GIAP the victor in Vietnam - MacDonald, Peter (Norton, 1993)
A portrait of one of the greatest military commanders of all time--from his early days as a resistance fighter against the Japanese through the brilliant campaigns against the French and Americans that established his reputation.
Keywords: Võ, Nguyên Giáp <1912->; Võ Nguyên Giáp -- 1910-2013; Vietnam. -- Quân đội nhân dân -- Biography; Oorlogen; Generals -- Vietnam -- Biography; Biografie